Randomized controlled trial comparing cefazolin with ceftriaxone in perioperative prophylaxis in orthopaedic surgeries - Kalawar, Rosan Prasad Shah; Shrestha, BP; Khanal, GP; Chaudhary, P; Rijal, R; Maharjan, R; Paneru, SR (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Surgical site infection is one of the most dreaded complications faced by an orthopaedic surgeon. In spite of cefazolin being recommended as perioperative antibiotic, many orthopaedic surgeons continue to use ceftriaxone as perioperative antibiotic.Objective: To compare the effectiveness of cefazolin and ceftriaxone as perioperative prophylactic antibiotics in the prevention of surgical site infection in clean elective orthopaedic surgeries.Methods: We conducted a randomized controlled trial in 197 patients undergoing clean elective orthopaedic surgeries. The patients were divided into two groups. One group received intravenous prophylactic antibiotics cefazolin and gentamicin and the other group received ceftriaxone and gentamicin in standard doses for 48 hours. Both groups were followed by oral Cephadroxyl for 7 days. The patients were followed up for three months.Results: There was no significant difference in the rate of surgical site infection among the two groups.Conclusion: We conclude that there is no difference in the effectiveness of prevention of surgical site infection between cefazolin and ceftriaxone.Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, page: 36-43